Plasma and blood volumes of dogs, determined by using RIHSA (Radioactive lodinated Human Serum Albumin) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1974)
Plasma and blood volumes of 9 dogs (5 male and 4 female)were determined by using RIHSA (Radioactive Iodinated Human SerumAlbumin). A positive correlation of high intensity was obtained when thevolume values were correlated with body weight of the animals. I t wasfound fo r male and female a value of 1,111 ml per each 10 kg of bodyweight.